2012
DOI: 10.3329/jdnmch.v18i1.12243
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom is an Ideal Food Supplement

Abstract: Mushroom, a nutrient-dense versatile food can share some of the benefits of fruits and vegetable and complement almost any everyday meal. Mushroom cultivation also requires low technology, low investment and can be grown in very little space. Due to culinary, nutritional and health benefits, the mushroom market is expected to grow as "a food, a tonic and a medicine". In the study food value of mushroom was found comparatively higher than that of other vegetables, fruits, meat and fish. This discussion suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 24 publications
(22 reference statements)
0
46
0
2
Order By: Relevance
“…Mushroom is also an excellent source of vitamin B12 (Koyyalamudi, Jeong, Cho, & Pang, 2009) which is generally not present in plant foods and ideal choice for the vegetarians. Owing to this balanced status of protein, fat, carbohydrate, minerals, vitamins, amino acids, and active ingredients, mushroom can be used as a substitute of meat, fish, fruits, and vegetables (Kakon, Choudhury, & Saha, 2012).…”
mentioning
confidence: 99%
“…Mushroom is also an excellent source of vitamin B12 (Koyyalamudi, Jeong, Cho, & Pang, 2009) which is generally not present in plant foods and ideal choice for the vegetarians. Owing to this balanced status of protein, fat, carbohydrate, minerals, vitamins, amino acids, and active ingredients, mushroom can be used as a substitute of meat, fish, fruits, and vegetables (Kakon, Choudhury, & Saha, 2012).…”
mentioning
confidence: 99%
“…Kakon et al (2012) reported that mushroom proteins contain all nine essential amino acids required by humans, enabling their use as a substitute for a meat diet. The amino acids found in A. bisporus in the highest amounts are alanine, aspartic acid, glutamic acid, arginine, leucine, lysine, phenylalanine, serine, proline, tyrosine and threonine (Muszyńska et al, 2013).…”
mentioning
confidence: 99%
“…100 to 200 g of mushrooms (dry weight) is required to maintain an optimal nutritional balance in a man weighing 70 kg. Protein value of mushrooms is twice as that of asparagus and potatoes, four times as that of tomatoes and carrots, and six times as that of oranges (Kakon et al, 2012). Mushrooms have been used as human food for centuries, being valued particularly for the variety of flavours and textures.…”
Section: Introductionmentioning
confidence: 99%